Linear and non-linear relationships between job demands-resources and psychological and physical symptoms of service sector employees. When is the midpoint a good choice? - Sanclemente, Francisco J.; Gamero, Nuria; Arenas, Alicia; Medina, Francisco J. (Frontiers in Psychology, 2022)
Related to the research of working conditions, the link between organizational factors and health was traditionally analysed using linear models. However, the literature analysis suggests inconsistencies in linear models predicting workers' health levels. To clarify this issue, this exploratory research compares the linear and nonlinear relationships between job demands-resources (task complexity, time pressure, contact with users, and job autonomy), and the psychological and physical symptoms of employees working in the main five service subsectors: commerce, horeca (hotels, restaurants, and cafés), public administration, education, and healthcare. With a final sample of 4047 participants, our study data were extracted from the II Andalusian Working Conditions Survey. Following the theoretical framework of JD-R Model and considering the Vitamin Model theoretical approach for nonlinear relationships, our results showed that there were significant differences among the five subsectors analyzed regarding the linear and nonlinear relationships between job demands-resources and psychological and physical symptoms of employees. Furthermore, task complexity generated nonlinear relationships in higher proportion than time pressure and contact with users. Likewise, nonlinear relationships found showed a U-shape. Moreover, the findings of nonlinear relationships suggested that medium levels of task complexity should not be exceeded to avoid further negative impact on psychological and physical symptoms for service sector employees, preserving their health. Finally, some general practical implications of work environment interventions are suggested.